Zero settlement risk token systems - Michael Junho Lee; Antoine Martin; Robert M. Townsend (Federal Reserve Bank of New York, 2024)
How might modern settlement systems with distributed ledger technology achieve zero settlement risk? We consider the design of settlement systems that satisfies two integral features: information-leakage proof and zero settlement risk. Legacy settlement systems partition private information but are vulnerable to settlement fails. A token system with dynamic ownership representation, or a dynamic ledger, can be designed to achieve both, as long as it employs a protocol that enforces two restrictions: programs must be immediately implemented and must involve transactions based on verifiable claims. We show how such a system can support various arrangements, including insurance, derivatives, collateralized loans, and securitization.
Keywords: G19; D86; D47; G29; 330; tokenization; programmability; settlement risk; financial architecture